Stated preferences for the colours, smells, and sounds of biodiversity - Peter M. King; Martin Dallimer; Thomas Lundhede; Gail E. Austen; Jessica C. Fisher; Katherine N. Irvine; Robert D. Fish; Zoe G. Davies (Ecological Economics, 2025)

Nature, smells, and human wellbeing - Phoebe R. Bentley; Jessica C. Fisher; Martin Dallimer; Robert D. Fish; Gail E. Austen; Katherine N. Irvine; Zoe G. Davies (Ambio, 2023)
The link between nature and human wellbeing is well established. However, few studies go beyond considering the visual and auditory underpinnings of this relationship, even though engaging with nature is a multisensory experience. While research linking smell to wellbeing exists, it focuses predominantly on smells as a source of nuisance/offence. Smells clearly have a prominent influence, but a significant knowledge gap remains in the nexus of nature, smell, and wellbeing. Here, we examine how smells experienced in woodlands contribute to wellbeing across four seasons. We show that smells are associated with multiple wellbeing domains, both positively and negatively. They are linked to memories, and specific ecological characteristics and processes over space/time. By making the link between the spatiotemporal variability in biodiversity and wellbeing explicit, we unearth a new line of enquiry. Overall, the multisensory experience must be considered by researchers, practitioners, policy-makers and planners looking to improve wellbeing through nature.

Kinematics of terrestrial locomotion in harbor seals and gray seals: Importance of spinal flexion by amphibious phocids - Jennifer N. Garrett; Frank E. Fish (Marine Mammal Science, 2015)
Pinnipeds are amphibious mammals with flippers, which function for both aquatic and terrestrial locomotion. Evolution of the flippers has placed constraints on the terrestrial locomotion of phocid seals. The detailed kinematics of terrestrial locomotion of gray ( Halichoerus grypus ) and harbor ( Phoca vitulina ) seals was studied in captivity and in the wild using video analysis. The seals exhibited dorsoventral undulations with the chest and pelvis serving as the main contact points. An anteriorly directed wave produced by spinal flexion aided in lifting the chest off the ground as the fore flippers were retracted to pull the body forward. The highest length‐specific speeds recorded were 1.02 BL /s for a gray seal in captivity and 1.38 BL /s for a harbor seal in the wild. The frequency and amplitude of spinal movement increased directly with speed, but the duty factor remained constant. Substrate did not influence the kinematics except for differences due to moving up or down slopes. The highly aquatic nature of phocids seals has restricted them to locomote on land primarily using spinal flexion, which can limit performance in speed and duration.

Development of consistently crossable wheat genotypes for alien wheat gene transfer through fine-mapping of the Kr1 locus - Isabelle Bertin; Lesley Fish; Tracie N. Foote; Emilie Knight; John Snape; Graham Moore (Theoretical and Applied Genetics, 2009)

Chemical Characterization of Territorial Marking Fluid of Male Bengal Tiger, Panthera tigris - B. V. Burger; M. Z. Viviers; J. P. I. Bekker; M. le Roux; N. Fish; W. B. Fourie; G. Weibchen (Journal of Chemical Ecology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Interferons and viruses - C. L. Galligan; T. T. Murooka; R. Rahbar; E. Baig; B. Majchrzak-Kita; E. N. Fish (Immunologic Research, 2006)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)

The relationship between diet and breast cancer in men (United States) - Karin A. Rosenblatt; David B. Thomas; L. Margarita Jimenez; Brian Fish; Anne McTiernan; Helge Stalsberg; Annette Stemhagen; W. Douglas Thompson; Mary G. McGrea Curnen; William Satariano; Donald F. Austin; Raymond S. Greenberg; et al. (Cancer Causes & Control, 1999)

Developments in cardiovascular ultrasound. Part 3: Cardiac applications - C. M. Moran; W. N. McDicken; P. R. Hoskins; P. J. Fish (Medical & Biological Engineering & Computing, 1998)

Application of natural and artificial fallout radionuclides to determining sedimentation rates in New Zealand lakes - N. E. Whitehead; R. G. Ditchburn; W. J. McCabe; W. J. Mason; J. Irwin; R. A. Pickrill; G. R. Fish (New Zealand Journal of Marine and Freshwater Research, 1998)
Sedimentation rates have been estimated for New Zealand Lakes Rotoiti, Taupo, Ngahewa, Tikitapu, Okareka, Pukaki, Rotorua, Waikaremoana, Wakatipu, Tekapo, and Ohau, and also the Falls Dam, Central Otago, the Pauatahanui inlet (Wellington), and Lake Vanda (Antarctica). Sedimentation rates were able to be calculated using the 210 Pb and 210 Po methods in 26 out of 28 cores. For the 137 Cs method (shown equivalent to the previous methods) calculable rates were obtained in 13 out of 19 cores. An age estimation was always possible by one of the methods. Values of 147 Pm and 144 Ce showed that most surface layers were undisturbed, hence the hypothetical mixing often invoked to explain 137 Cs profiles lacking the expected 1965 peak is incorrect for most of these cores. Deficits in surface layer 210 Pb caused by 222 Rn loss did not affect the estimates of sedimentation rate. One core contained a record dated back to 1800 A.D. Deposition rates of 210 Pb depended on rainfall, not river input. Some local geothermal activity emits 222 Rn and deposits more 210 Pb than usual for New Zealand lakes, but otherwise absolute 210 Pb levels are generally very low compared to other studies. Deposition rates varied from a low of 0.11 kg m‐ 2 yr‐1 (Lake Tikitapu) to a high of 28 kg m‐ 2 yr‐ 1 (one Lake Pukaki core).

Developments in cardiovascular ultrasound. Part 2: Arterial applications - P. R. Hoskins; P. J. Fish; W. N. McDicken; C. Moran (Medical & Biological Engineering & Computing, 1998)

Developments in cardiovascular ultrasound: Part 1: Signal processing and instrumentation - P. J. Fish; P. R. Hoskins; C. Moran; W. N. McDicken (Medical & Biological Engineering & Computing, 1997)

Variability in potato tissue culture - A. Karp; M. G. K. Jones; D. Foulger; N. Fish; S. W. J. Bright (American Journal of Potato Research, 1989)